2021
DOI: 10.26656/fr.2017.5(3).572
|View full text |Cite
|
Sign up to set email alerts
|

Effect of three types of oils and their level of incorporation on sensory quality of sorghum cookies

Abstract: Lipid (oil and fat) is one of the basic and important components used in the production of cookies. It plays several roles in their composition and a judicious choice of this ingredient makes it possible to have cheap, delicious and very nutritious cookies. This study aimed to evaluate the effect of refined cottonseeds oil (RCO), refined palm oil (RPO) and red (or crude) palm oil (CPO) on sorghum (Sorghum bicolour var. Gampela) cookies. Oils were incorporated at levels of 16%, 20% and 24%. Cookies quality were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…RPO addition to increase carotenoid content of food has been carried out by previous researchers with different concentrations depending on the type of food. Sorghum cake containing 20% RPO was preferred over the cake with 24% RPO [ 34 ] and beef sausages with 10% RPO were more acceptable than those with 15% RPO [ 35 ]. In this study, based on the panel's discussion, it was concluded that adding 2% RPO, either before or after cooking, could be used as a cooking method to produce rice with a sensory quality similar to or better than regular rice.…”
Section: Resultsmentioning
confidence: 99%
“…RPO addition to increase carotenoid content of food has been carried out by previous researchers with different concentrations depending on the type of food. Sorghum cake containing 20% RPO was preferred over the cake with 24% RPO [ 34 ] and beef sausages with 10% RPO were more acceptable than those with 15% RPO [ 35 ]. In this study, based on the panel's discussion, it was concluded that adding 2% RPO, either before or after cooking, could be used as a cooking method to produce rice with a sensory quality similar to or better than regular rice.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have shown the influence of fat on colouring. Goubgou et al [48] studied sorghum cookies prepared with refined cottonseed oil, refined palm oil and crude palm oil (16%, 20% and 24% in the recipe, respectively), and found browning on all cookies, with yellowing on cookies produced with red palm oil. In addition, they found that the higher the fat content in the recipe, the higher the browning intensity.…”
Section: Colour Of Fatmentioning
confidence: 99%
“…On the other hand, some other sources of fat such as palm oil and cottonseed oil are more accessible to the poorest people. Also, our earlier work [20] therefore evaluated the effect of refined cottonseed oil (RCO), refined palm oil (RPO) and crude palm oil (CPO) and their level of incorporation on sensory quality of sorghum cookies have presented good acceptability. The aim of the present study was to evaluate the RCO, RPO, and CPO on the physicochemical characteristics of sorghum cookies comparatively to a margarine (M20) cookies.…”
Section: Introductionmentioning
confidence: 99%